Dysregulated miRNAs in bone cells of patients with Gorham‐Stout disease. Issue 3 (20th February 2021) - Rossi, Michela; Rana, Ippolita; Buonuomo, Paola Sabrina; Battafarano, Giulia; Mariani, Eda; D'Agostini, Matteo; Porzio, Ottavia; De Martino, Viviana; Minisola, Salvatore; Macchiaiolo, Marina; De Vito, Rita; Vecchio, Davide; et al.
Abstract: Gorham‐Stout disease (GSD) is a very rare disease characterized by increased bone erosion with angiomatous proliferation. The mechanisms underlying this disorder have not been deeply investigated. Due to its rarity, no guidelines are currently available for treatment and management of GSD. We recently evaluated the cellular alterations of the bone remodeling in patients showing that osteoclast precursors displayed increased ability to differentiate into osteoclasts and that affected osteoclasts resorb bone more actively than control cells. Moreover, osteoblasts isolated from a patient showed a defective ability to form mineralized nodules. In this paper, we investigated the molecular pathways involved in the cellular defects of GSD bone cells. For this study, we recruited nine patients and performed miRNome analysis of bone cells. Between the 178 miRNAs robustly expressed in GSD osteoclasts, significant modulation of three miRNAs (miR‐1246, miR‐1‐3p, and miR‐137‐3p) involved in the regulation of osteoclast formation and activity or in the angiomatous proliferation was found in patients' cells. Interestingly, miR‐1246 was also up‐regulated in serum exosomes from patients. Analysis of miRNAs from patient osteoblasts suggested alteration of miR‐204a‐5p, miR‐615‐3p and miR‐378a‐3p regulating osteoblast function and differentiation. The resulting miRNA pattern may help to understand better the mechanisms involved in GSD and to identify new potential therapeutic targets for this rare disease.